2019
DOI: 10.2147/cmar.s190999
|View full text |Cite
|
Sign up to set email alerts
|

<p>Wnt5a induces ROR1 and ROR2 to activate RhoA in esophageal squamous cell carcinoma cells</p>

Abstract: Background: Wnt5a is a nontransforming Wnt family member and identified as an oncogenic role on cell motility of breast cancer and glioblastoma. However, Wnt5a signaling in esophageal squamous cell carcinoma (ESCC) progression remains poorly defined. Materials and methods: Immunohistochemistry assays were used to measure the Wnt5a expression in ESCC sections. We evaluated the role of receptor tyrosine kinase-like orphan receptor (ROR)1/2 and RhoA on the invasion of ESCC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
(43 reference statements)
1
19
0
Order By: Relevance
“…Many researchers have sought to determine the role of RhoA in the occurrence and development of cancers.Surveys such as that conducted by Kalpana et al show thatRhoA knockdown promotes breast cancer metastasis 28. Wnt5a promotes migration and metastasis of breast cancer and esophageal squamous cell carcinoma cells by activating RhoA 29,30. Our data verified that ANLN promoted RhoA activation by interacting with RhoA in MDA-MB-231 and MDA-MB-231/ADM cells.…”
supporting
confidence: 82%
“…Many researchers have sought to determine the role of RhoA in the occurrence and development of cancers.Surveys such as that conducted by Kalpana et al show thatRhoA knockdown promotes breast cancer metastasis 28. Wnt5a promotes migration and metastasis of breast cancer and esophageal squamous cell carcinoma cells by activating RhoA 29,30. Our data verified that ANLN promoted RhoA activation by interacting with RhoA in MDA-MB-231 and MDA-MB-231/ADM cells.…”
supporting
confidence: 82%
“…In vitro experiments confirmed that hTERT knockdown suppresses the migration and invasion abilities of ESCC cells, and suppresses the colony-formation ability of Kyse410 cells. The previous study reported that Wnt5a promotes ESCC cell invasion via retinoic acid-related orphan receptors (ROR)1 and ROR2 and disheveled-associated activator of morphogenesis 1/RhoA signaling pathway ( 60 ), thus the potential association between hTERT, Wnt5a and ROR needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand stimulation can either induce ROR1/ROR2 homo- or heterodimerization [ 15 , 136 , 137 ], or their association with FZD receptors [ 127 , 138 , 139 ]. Moreover, in HEK293 cells, ROR2, but not ROR1, was found to form a complex with PTK7 and WNT5A, which activated JNK and AP-1 [ 140 ].…”
Section: Wnt/ror Signaling At a Glancementioning
confidence: 99%
“…This is also true for WNT/ROR signaling [ 56 , 70 , 91 , 114 , 121 ]. Activated DVL proteins can relay the signals to distinct signaling branches centered around the small GTPases RHO, RAC and CDC42 which become activated upon WNT/ROR stimulation [ 15 , 56 , 57 , 102 , 137 ]. The regulation was even observed in vivo as a gene set enrichment analysis showed that pre-treatment CLL samples displayed a higher expression of genes associated with activation of RAC1 or RHOA than matched samples after treatment with the ROR1-blocking antibody cirmtuzumab [ 112 ].…”
Section: Wnt/ror Signaling At a Glancementioning
confidence: 99%